Optimizing The Role Of The Indonesian National Army In Addressing The Crime Of Terrorism - Slamet Tri Wahyudi; Syamsul Hadi; Aji Lukman Ibrahim (Faculty of Law, Pembangunan Nasional Veteran Jakarta University, 2022)
The role of the Indonesian National Army (Tentara Nasional Indonesia “TNI”) in countering terrorism is part of the strategy to combat terrorism. With the escalation of the threat of terrorism which not only threatens national security, but also state sovereignty, the involvement of the TNI is a necessity in order to defend the country from threats or terrorist attacks. This study describes the urgency of the TNI's involvement in efforts to overcome acts of terrorism that threaten state sovereignty, and how the ideal role of the TNI in efforts to combat criminal acts of terrorism is described. The method used in this research is normative legal research, using a statutory approach (statute approach) and a conceptual approach (conceptual approach). The results of this study indicate that there is a need for regulations that clarify the main tasks and functions of the TNI in combating terrorism. The proposed efforts to involve the TNI in counter-terrorism include aspects of enforcement and prevention. In the aspect of prosecution, the technical involvement of the TNI in counter-terrorism operations is at the back, when the Anti-Terror Detachment 88 is in a condition beyond over capacity and the gradation of threats that endangers the sovereignty of the state. In the prevention function, the role of the TNI is more focused on the effective use of intelligence forces in supporting the prevention of criminal acts of terrorism. Technically, the role of the TNI that must be carried out is early warning, early prevention, and prosecution and restoration of an area as a result of acts of terrorism.